Pirates in paradise a modern history of Southeast Asia's maritime marauders - Eklof, Stefan (Studies in contemporary Asian history, 2006)
This text traces the shifting character and development of Southeast Asian piracy from the 18th century to the present day, demonstrating how political, economic, social and technological factors have contributed to change - but have by no means exterminated - the phenomenon.